2014
DOI: 10.1039/c3ay42029a
|View full text |Cite
|
Sign up to set email alerts
|

A XANES study of chromophores: the case of black glass

Abstract: In the 1st–2nd century AD, glass was made black using strongly reducing conditions. Later, the black appearance was obtained adding an excess of colourant rather than controlling the furnace atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…The Raman spectrum of glass consists of two broad bands, one around 500 cm -1 (SiO 4 bending vibrations), and one around 1000 cm -1 (SiO 4 stretching vibrations). Previous studies on glass and glass beads [4,[11][12][13][14][15][16] ak maxima from this s taining only ed in Fig. 4 seen in Fig.…”
Section: Raman and Xrf Results For The Glass Matrixmentioning
confidence: 68%
“…The Raman spectrum of glass consists of two broad bands, one around 500 cm -1 (SiO 4 bending vibrations), and one around 1000 cm -1 (SiO 4 stretching vibrations). Previous studies on glass and glass beads [4,[11][12][13][14][15][16] ak maxima from this s taining only ed in Fig. 4 seen in Fig.…”
Section: Raman and Xrf Results For The Glass Matrixmentioning
confidence: 68%
“…Data from this study 13‐1: ◯; 13‐2: ▵; 13‐3: ◇; 13‐4: ◻ as original (black plain symbols). Data from previous studies are reported: ❋, ×, ⧖, ▽, black symbols: blue and blue‐green glasses, gray symbols: other colors. Three domains (i), (ii) and (iii) are distinguished (see discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The redox state of TM elements depends on glass fabrication conditions (furnace temperature and atmosphere) and glass chemical composition . The atmosphere of ancient furnaces is assumed to be reducing because of combustion conditions . However, the absence of quantitative estimates of the oxygen partial pressure limits our knowledge on the know‐how of glassmakers concerning melting and fining conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, apart from producing delicate vessels, Roman glassmakers were also able to control the production parameters to achieve certain colours. Iron, being a sand impurity, is always present in Roman glass in a rather reduced form, thus causing the glass to have a bluish colour with an absorption peak at 1100 nm (Ceglia et al, 2014). Through the addition of antimony or manganese oxides, iron in glass was oxidised to its yellowish form (main absorption peaks at 380, 420 and 435 nm) thus giving the impression of a colourless glass (Foster and Jackson, 2010;Jackson, 2005).…”
Section: Introductionmentioning
confidence: 99%